Identification and characterization of Chlamydia trachomatis type III secretion substrates - Cunha, Maria Sarmento de Matos Paiva Raposo da (2016)
Chlamydiae are a large group of Gram-negative obligate intracellular bacteria that only grow within a membrane-bound vacuole in eukaryotic host cells. All Chlamydiae share a unique biphasic developmental cycle, in which the non-replicative elementary bodies (EBs) invade host cells and remain restricted within the bacterial vacuole, known as inclusion. Soon after invasion, EBs develop into replicative RBs that grow and divide by binary fission. Later in the cycle, RBs undergo a secondary differentiation into EBs, which are released from the host cell to initiate new rounds of invasion.(...)